Phytochemical profiles and anti-diabetic benefits of two edible Amaranthus species - Ya-Chen Yang; Mei-Chin Mong; Wen-Tzu Wu; Zhi-Hong Wang; Mei-Chin Yin (CyTA - Journal of Food, 2020)
Phytochemical profile and activity of anti-oxidative, anti-glycative, anti-α-amylase, anti-α-glucosidase, anti-lipase and anti-acetylcholinesterase (AchE) of aqueous extracts prepared from leaf and stem parts of two edible Amaranthus species, white and red amaranths, were investigated. Phytochemical analyses showed that white amaranth had more total phenolic acids than red one. The content of total flavonoids in four examined aqueous extracts was similar. Red amaranth has greater anthocyanins and carotenoids than white one. All aqueous extracts at three concentrations were used for in vitro bio-activities experiments. Results showed that four aqueous extracts displayed radical scavenging effect, Fe2+ chelating effect, xanthine oxidase inhibition, and reducing power. Aqueous extracts prepared from red amaranth exhibited marked anti-glycative effects, anti-α-amylase, anti-α-glucosidase, anti-lipase, and anti-AchE activities. These findings suggested that these two vegetables could be developed as functional foods for diabetic prevention and/or attenuation.